Probing the degradation and homogeneity of embedded perovskite semiconducting layers in photovoltaic devices by Raman spectroscopy - Katherine Hooper (Physical Chemistry Chemical Physics, 2017)
The key challenges for perovskite solar cells include their poor stability and film homogeneity. Studying the degradation and homogeneity of perovskite layers within device structures can be challenging but critical to the understanding of stability and effect of processing in real life conditions. We show that Raman spectroscopy (RS) is a unique and powerful method (simple and fast) to probe the degradation of the perovskite film within the device structure and image perovskite formation. We demonstrate that RS can be used to directly probe chemical (PbI2) and physical (dihydrated phase) degradation of a perovskite film, and estimate the relative amount of the degradation species formed, mapping its distribution with ∼1 μm spatial resolution. This has been applied to mapping a large area perovskite module to characterise the efficacy of PbI2 to perovskite conversion. We also use RS to study the degradation species and kinetics under diverse accelerated degradation conditions (temperature and humidity) in situ. These capabilities are difficult to achieve with other methods, presenting RS as an important tool to gain understanding of the degradation and effect of processing on perovskite-based photovoltaic devices.